2010
DOI: 10.1088/0965-0393/18/8/085006
|View full text |Cite
|
Sign up to set email alerts
|

Surface effect on the self-equilibrium state and size-dependent elasticity of FCC thin films

Abstract: On the {1 1 0} solid surface, surface stresses of two perpendicular directions, such as ⟨1 0 0⟩ and ⟨1 1 0⟩, will differ. These different surface stresses cause different equilibrium strains in the ⟨1 0 0⟩ and ⟨1 1 0⟩ directions on a {1 1 0} thin film. In this paper, an analytical formulation is presented to predict the equilibrium strains of orthotropic thin films with {1 0 0}, {1 1 1} or {1 1 0} surfaces. This formulation is composed of the elastic constants of bulk materials and surface parameters such as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…The size effects on Young's modulus observed in experiments have also been seen in computer simulations which also have reported size effects on Poisson's ratio [21][22][23]. Furthermore, computer simulations have also observed that strain rate influences the elastic response [24][25][26].…”
Section: Introductionsupporting
confidence: 54%
“…The size effects on Young's modulus observed in experiments have also been seen in computer simulations which also have reported size effects on Poisson's ratio [21][22][23]. Furthermore, computer simulations have also observed that strain rate influences the elastic response [24][25][26].…”
Section: Introductionsupporting
confidence: 54%
“…[2009] proposed a continuum-based bridging model for a nanofilm using the surface elasticity model by Gurtin and Murdoch [1975;1978]. Cho et al [2009] suggested a sequential multiscale method in order to determine initial surface stress and surface Lamé constants using a matching method based on a molecular dynamics (MD) simulation.…”
Section: Wonbae Kim Seung Yun Rhee and Maenghyo Chomentioning
confidence: 99%
“…It is well known that the mechanical properties of a nanosized structure significantly differ from those of bulk materials because of the surface effect. Therefore, although the surface effect is negligible in macroscale studies, it is crucial for a nanosized structure analysis to account for the influence of the surface effect [Miller and Shenoy 2000;Zhou and Huang 2004;Diao et al 2004;Liang et al 2005;Guo and Zhao 2005;Sun and Zhang 2005;Dingreville et al 2005;Wang et al 2008;He and Lilley 2008;Zhang et al 2008;Dingreville et al 2008;Park 2009;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the mechanical properties of a nanosized structure significantly differ from those of bulk materials because of the surface effect. Therefore, although the surface effect is negligible in macroscale studies, it is crucial for a nanosized structure analysis to account for the influence of the surface effect [Miller and Shenoy 2000;Zhou and Huang 2004;Diao et al 2004;Liang et al 2005;Guo and Zhao 2005;Sun and Zhang 2005;Dingreville et al 2005;Wang et al 2008;He and Lilley 2008;Zhang et al 2008;Dingreville et al 2008;Park 2009;.…”
Section: Introductionmentioning
confidence: 99%